2018
DOI: 10.3389/fpsyt.2018.00094
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Cerebral Microbleeds and Depression in the General Elderly Population: A Meta-Analysis

Abstract: BackgroundIt remains unclear whether cerebral microbleeds (CMBs) are associated with depression in the general elderly population. We thus performed a meta-analysis to evaluate the relationship between depression and CMBs.MethodsA systematic literature search was conducted in EBSCO, PubMed, and Web of Science for relevant studies that assessed the relationship between depression and the prevalence of CMBs.ResultsFive eligible studies including 7,328 patients were pooled in meta-analysis. The prevalence of CMBs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 30 publications
1
7
1
Order By: Relevance
“…However, the effect of an mTBI, which is the most frequent form of brain trauma, on the development of CMBs in aging, has not been established ( Wang et al, 2014 ; Krishnamoorthy et al, 2015 ; Rauen et al, 2020 ). Here, we show ( Figure 2 ) that significantly more microbleeds can be found in aging human brains than in the brains of young healthy individuals, confirming the results of previous studies ( Greenberg et al, 2009 ; Werring et al, 2010 ; Toth et al, 2015 ; Akoudad et al, 2016 ; Wang et al, 2018 ). We also found significantly more CMBs in elderly patients after an mTBI compared with young patients with an mTBI; however, we did not observe a significant difference in the number of cerebral microhemorrhages between aged and aged patients with mTBIs.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…However, the effect of an mTBI, which is the most frequent form of brain trauma, on the development of CMBs in aging, has not been established ( Wang et al, 2014 ; Krishnamoorthy et al, 2015 ; Rauen et al, 2020 ). Here, we show ( Figure 2 ) that significantly more microbleeds can be found in aging human brains than in the brains of young healthy individuals, confirming the results of previous studies ( Greenberg et al, 2009 ; Werring et al, 2010 ; Toth et al, 2015 ; Akoudad et al, 2016 ; Wang et al, 2018 ). We also found significantly more CMBs in elderly patients after an mTBI compared with young patients with an mTBI; however, we did not observe a significant difference in the number of cerebral microhemorrhages between aged and aged patients with mTBIs.…”
Section: Discussionsupporting
confidence: 90%
“…It has been shown previously that both TBIs and aging induce the development of CMBs ( Huang et al, 2015 ; Toth et al, 2015 ; Ungvari et al, 2017 ; Irimia et al, 2018 ; Wang et al, 2018 ; Griffin et al, 2019 ). In both cases, CMBs are associated with long-term cognitive deficits and gait dysfunctions and determine the outcome of patients ( Werring et al, 2010 ; de Laat et al, 2011 ; Huang et al, 2015 ; Toth et al, 2015 , 2020 ; Yakushiji, 2015 ; Akoudad et al, 2016 ; Ungvari et al, 2017 , 2018 ; Irimia et al, 2018 ; Nyúl-Tóth et al, 2020 ).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Papers were automatically identified by searching the terms throughout the published text. All output results were generated by WoS and utilized the same result exploitation search strategy as used in other studies (e.g., Chang et al, 2017;Walls, 2018;Wang et al, 2018;Zhao et al, 2018).…”
Section: Frequent Use Of the Term "Morphological Variability" In Coasmentioning
confidence: 99%
“…Depressive symptoms have been associated with several indicators of poor brain health, such as smaller hippocampi, smaller subcortical structure volume, and more cortical thinning (Binnewies et al, 2021;Kempton et al, 2011;Schmaal et al, 2020). Particularly in the elderly (age above 60), a greater presence of markers of cerebrovascular disease (Kales et al, 2005) has been reported, presented as more cerebral microbleeds (Wang et al, 2018), white matter lesions (Herrmann et al, 2008), and lacunar infarcts (Valkanova and Ebmeier, 2013). Findings have however been somewhat inconsistent, with some studies not replicating associations of depressive symptoms with smaller total brain volume or subcortical structure volume (e.g.…”
Section: Introductionmentioning
confidence: 99%